Congress on Technical Advancement 2017. proceedings of the 17th International Conference on Cold Regions Engineering presented at the First Congress on Technical Advancement : September 10-13, 2017, Duluth, Minnesota - Zufelt, Jon E. (American Society of Civil Engineers, 2017)
This collection contains 20 peer-reviewed papers on cold regions engineering. Topics include: material characteristics at low temperatures; ground freezing assessment; permafrost, ground ice, and sea ice; and pavement systems in cold regions.